How to communicate bad news in times of pandemic - Rodolfo Isidro Bosch Bayard; Miguel Angel Blanco Aspiazu; Ana Lidia Rodriguez Blanco (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Humanity has been surprised by the impact of the COVID-19 pandemic; its contagiousness and lethality are great causes for concern around the world.  In this context, it is very difficult for the health personnel to communicate bad news. Objective: To express the need to develop skills among the health care personnel to communicate bad news in the context of the COVID-19 pandemic. Material and Methods: A bibliographic review about the impact of the COVID-19 pandemic on mental health and the need to prepare the health personnel to communicate bad news was carried out. Results: Reactions of depression, anxiety, sleep disorders and post-traumatic stress caused by this pandemic have been described. Several protocols that can be followed when performing this practice are described; they include: The Buckman, Spikes and ABCDE protocols. Conclusions: The COVID-19 pandemic has caused great effects on the mental health of the general population around the world. Therefore, it is necessary for the health personnel to be well trained in communicating bad news, as well as to create suitable spaces for this practice.  On the other hand, the institutions should design and implement their action protocols to carry out this task.